2020
DOI: 10.4236/gep.2020.83010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sediment and Benthic Macrofauna Distribution at Dar es Salaam Harbour Channel

Abstract: Sediment and macrobenthic fauna distribution at Dar es Salaam harbour channel were investigated to attest the influence of sediment grain size distribution and total organic carbon contents on benthic macrofauna dominance and diversity. Sampling campaign was conducted from January to April, 2019 in 25 sampling stations along the channel. Sediment grain sizes ranged between 0.7405 and 0.00273 mm with an average of 0.0804 mm classified as medium silt. Sediment distribution showed an onshore-offshore pattern cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The concentrations of Ni were below all the recommended environmental quality targets, despite the fact that Ni and Pb are among the elements found in petroleum products, lubricants and marine diesel oil (Mihale 2017(Mihale , 2019. This indicated that low Ni was due to low carbon content in sediments to complex more Ni (Mrutu et al 2013, Silva et al 2019.However, the overall trend of heavy metal distribution was decreasing offshore, a trend similar to that observed by Mrutu et al (2013), Mihale (2017), andSilva et al (2019), associated with the changes in sediment grain size from clay-silt to sandy-pebble offshore (Mwakisunga et al 2020).…”
Section: Heavy Metals Total Concentrations In Sedimentsmentioning
confidence: 68%
“…The concentrations of Ni were below all the recommended environmental quality targets, despite the fact that Ni and Pb are among the elements found in petroleum products, lubricants and marine diesel oil (Mihale 2017(Mihale , 2019. This indicated that low Ni was due to low carbon content in sediments to complex more Ni (Mrutu et al 2013, Silva et al 2019.However, the overall trend of heavy metal distribution was decreasing offshore, a trend similar to that observed by Mrutu et al (2013), Mihale (2017), andSilva et al (2019), associated with the changes in sediment grain size from clay-silt to sandy-pebble offshore (Mwakisunga et al 2020).…”
Section: Heavy Metals Total Concentrations In Sedimentsmentioning
confidence: 68%